2020
DOI: 10.1177/0972063420935539
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Preparedness and Resilience in Public Health Emergencies at District Hospitals and Community Health Centres

Abstract: Background: Public health emergencies (PHE) caused by natural hazards spread from one particular locality to adjacent geographic areas and then encompass the entire planet in today’s fast global connectivity mode. Each country, including India, has its own set of potential disasters based on the hazards present as well as the unique vulnerabilities of the community and community’s preparedness to respond to particular disasters. Currently, human history is observing a very critical time fighting an invisible e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…Strengthening the managerial competencies of hospital leaders in the face of outbreaks such as COVID-19 is found to be among the most critical lessons learned from the pandemic (59). This is similar to studies from Iran, India and the Philippines, where strong leadership enabled hospital preparedness and resilience (34,46,60). In addition to this, the pandemic further highlighted the importance of coordination with other hospitals, local authorities, and disaster management agencies, functional information systems (which adapt new technologies), and internal and external communication with the community, media, civic organizations, and local authority, particularly for risk communication and community engagement (3,15).…”
Section: Componentssupporting
confidence: 67%
See 1 more Smart Citation
“…Strengthening the managerial competencies of hospital leaders in the face of outbreaks such as COVID-19 is found to be among the most critical lessons learned from the pandemic (59). This is similar to studies from Iran, India and the Philippines, where strong leadership enabled hospital preparedness and resilience (34,46,60). In addition to this, the pandemic further highlighted the importance of coordination with other hospitals, local authorities, and disaster management agencies, functional information systems (which adapt new technologies), and internal and external communication with the community, media, civic organizations, and local authority, particularly for risk communication and community engagement (3,15).…”
Section: Componentssupporting
confidence: 67%
“…Across the literature, hospital preparedness is highlighted as the most essential stage of the DRM cycle (19,22,34,35,41,46,52,60). One systematic review on hospital resilience found that more than half of included studies mentioned hospital planning and preparedness, indicating the bias the literature toward preparedness as a stepping-stone to resilience (22).…”
Section: Preparednessmentioning
confidence: 99%
“…Frontliners aptly noted the hospital's role in fulfilling their primary functions in service delivery but also additional functions in health promotion, community engagement, and risk mitigation. This is consistent with global literature on hospitals during health emergencies where the primary objective of resilient hospitals is to "maintain their function, which occurs when they provide quality (safe, effective, patient-centered, timely, efficient, equitable) and continuous critical and essential services, amidst the crises, while leaving no one behind" (2,(21)(22)(23)(24). Whereas historically public health functions have been associated with primary care; recent evidence on building resilient health systems to achieve UHC and health security highlights the contributions of all health systems actors (including hospitals) in fulfilling EPHF (13).…”
Section: Discussionsupporting
confidence: 82%
“…Disaster preparedness [ 27 ] and preparedness education [ 29 , 32 ] are national priorities [ 29 ], for which the policy is usually implemented by local departments [ 34 , 35 ]. Infrastructure [ 30 , 40 ], resources [ 33 , 36 , 41 ], as well as planning and warning communication [ 33 , 35 ] are indispensable elements of community resilience in disasters. For cross-regional disaster prevention, neighbors might function as resources for disaster preparedness [ 39 ], and cross-regional organizational relations could enhance resilience in each hierarchical and horizontal emergency management network [ 42 ].…”
Section: Literature Reviewmentioning
confidence: 99%